Nilai-Nilai Al-Quran Surat Thaha Ayat 132 terhadap Tanggung Jawab Orang Tua dalam Pendidikan Agama Anak - Rofiah; Dedih Surana (Bandung Conference Series: Islamic Education, 2022)
Abstract. Allah SWT revealed Surah Thaha verse 132. Allah commanded Rasulullah SAW in this verse so that he invites all family members to perform prayers. Based on this, there is a problem formulation, namely (1) What are the opinions of the commentators about the main content of the Al-Quran Surah Thaha verse 132? (2) What is the essence in the Quran? (3) How do experts view parental responsibility? on children's religious education in the Al-Quran Surah Tahaha verse 132? (4) What are the educational values and implications of Al-Quran Surah Thaha verse 132 on the responsibilities of parents in children's religious education? This study uses a descriptive-analytical method of collection technique, namely library research by examining in depth various interpretations. T has been regulated in law no. 1 of 1974 concerning the main points of marriage, article 45 paragraph 1, namely: "both parents are obliged to maintain and educate their children as well as possible". In this research, it was concluded that parents are responsible for the religious education of they children, one of which is to educate and foster children to establish prayers, in educating children to pray requires patience. The peak he achieved was the victory of the soul. The values in Surah Thaha verse 132 are (1) The head of the family is ordered by Allah to educate, foster, guide his family responsibilities in establishing prayer (2) In educating children or families to pray, patience is needed with earnest intentions (3 ) Allah will provide and fulfill all facilities also needs if parents have the intention and sincerity in educating their children. (4) Humans who endeavor with full sincerity in educating their children to pray, Allah will give the best reward.. Abstrak. Allah SWT menurunkan surat Thaha ayat 132. Allah memerintahkan kepada Rasulullah SAW pada ayat ini supaya beliau mengajak seluruh anggota keluarga untuk menunaikan salat. Berdasarkan tersebut maka terdapat rumusan masalah yaitu (1) Bagaiman pendapat para mufasir tentang pokok kandungan Al-Quran surat Thaha ayat 132? (2) Bagaimana esensi dalam Al-Quran? (3) Bagaimana pandangan para ahli tentang tanggung jawab orang tua? terhadap pendidikan agama anak dalam Al-Quran surat Thaha ayat 132? (4) Bagaimana nilai-nilai dan implikasi pendidikan Al-Quran surat Thaha ayat 132 terhadap tanggung jawab orang tua dalam pendidikan agama anak?. Penelitian ini menggunakan metode deskriptif-analitis teknik pengumpulan yaitu kepustakaan (library research) dengan mengkaji secara mendalam berbagai tafsir, buku dan artikel. Telah diatur dalam undang-undang No. 1 tahun 1974 tentang pokok-pokok perkawinan pasal 45 ayat 1, yaitu: “kedua orang tua wajib memelihara dan mendidik anak-anak mereka sebaik-baiknya”. Dari penelitian ini, diperoleh simpulan bahwa orang tua bertanggung jawab dalam pendidikan agama seorang anak, salah satunya yaitu untuk mendidik serta membina anak agar mendirikan sholat. Nilai-nilai dalam surat Thaha ayat 132 adalah (1) Kepala keluarga diperintahkan oleh Allah untuk mendidik, membina, membimbing tanggung jawab keluarga nya dalam mendirikan shalat (2) Dalam mendidik anak atau keluarga untuk shalat diperlukan kesabaran dengan niat yang sungguh-sungguh (3) Allah akan memberikan serta mencukupi segala fasikitas dan kebutuhan apabila orangtua memiliki niat dan kesungguhan dalam mendidik anak (4) Manusia yang berikhtiar dengan penuh kesungguhan dalam mendidik anaknya untuk melaksanakan shalat maka Allah akan memberikan balasan yang terbaik.